Letter from World University Service on Educational Background of Refugee Hungarian Students - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): World University Service Letter from World University Service to UN describes nature of Hungarian students' educational background and warns receiving countries to take this into consideration when offering scholarships and preparing to receive Hungarian Students. Letter also provides update on coordination of activities related to Hungarian students with Austria, Switzerland and France.